Measuring Employee Performance Post Pandemi Covid-19 View From Motivation, Competence, Discipline and Work Environment at Palang Merah Indonesia (PMI) Klaten Regency - I Wayan Sahopiartha, I Wayan Sahopiartha; Bambang Mursito, Bambang Mursito; Sarsono, Sarsono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study used a quantitative descriptive approach. The author chooses to use this quantitative descriptive method to determine the amount of influence and significance between the variables of competence, motivation, work discipline, culture and work environment on employee performance. The research was conducted at the Indonesian Red Cross Office (PMI) Klaten Regency which is located at Jalan Veteran No. 80 North Klaten, Klaten - Central Java 57431, Indonesia, the research time was carried out for 6 (six) months. The population in this study is all PMI employees of Klaten Regency totaling 60 people. The sample taken in this study was as many as 60 respondents The sampling technique used in this study was a census technique. The census method is a sampling technique when all members of the population are used as samples. After getting answers from respondents, the data is then processed using multiple linear regression analysis tools with the help of SPSS 23 software. Based on the results of the discussion above, the following conclusions can be drawn that have a significant effect on the performance of PMI Employees of Klaten Regency after the Covid-19 Pandemic. However, it did not have a significant effect on the performance of PMI Employees of Klaten Regency after the Covid-19 Pandemic